2017
DOI: 10.4049/jimmunol.1601291
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Cell-Type Differences in the Epithelial Secretome Reveals Insights into the Pathogenesis of Respiratory Syncytial Virus–Induced Lower Respiratory Tract Infections

Abstract: Lower respiratory tract infections (LRTIs) from Respiratory Syncytial Virus (RSV) are due, in part, to secreted signals from lower airway cells that modify immune response and trigger airway remodeling. To understand this process, we applied an unbiased quantitative proteomics analysis of the RSV-induced epithelial secretory response in cells representative of the trachea (hBECs) vs small airway bronchiolar cells (hSAECs). A workflow was established using telomerase- immortalized human epithelial cells that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 82 publications
1
95
0
Order By: Relevance
“…2G). We also examined the presence of RSV virions in cellular supernatants using selective SRM-MS assays developed by us previously (29). All RSV proteins were detected in the supernatant in patterns identical to that shown for RSV N protein, where cells treated with JQ1 had slightly higher levels of RSV proteins (Fig.…”
Section: Brd4 Is Functionally Required For Rsv-mediated Induction Of mentioning
confidence: 69%
See 1 more Smart Citation
“…2G). We also examined the presence of RSV virions in cellular supernatants using selective SRM-MS assays developed by us previously (29). All RSV proteins were detected in the supernatant in patterns identical to that shown for RSV N protein, where cells treated with JQ1 had slightly higher levels of RSV proteins (Fig.…”
Section: Brd4 Is Functionally Required For Rsv-mediated Induction Of mentioning
confidence: 69%
“…hSAECs are immortalized with human telomerase and CDK4 expression; these maintain a stable epithelial morphology, express differentiated cytokeratin (CK) isoforms, form pseudostratified columnar epithelial structures, undergo cell cycle arrest, and transition into mesenchymal cells like primary bronchiolar cells (26)(27)(28). Moreover, hSAECs have similar genomic signatures and exhibit similar RSV-induced innate responses as those of primary SAECs (22,27,29). Upon RSV adsorption, the initiation of RSV transcription triggers the innate response.…”
Section: Rsv Induces Changes In the Brd4 Abundance Associated With Nfmentioning
confidence: 99%
“…This model used telomerase-immortalized human small airway epithelial cells (hSAECs), differentiated epithelial cells that exhibit similar innate responses as primary SAECs whose stable phenotype enables genomic manipulation. hSAECs permit study of signalling pathways relevant to those in vivo (Tian et al, 2017; Zhao et al, 2017). To establish stable RelA-deficient hSAECs, we used CRISPR/Cas9 genome editing to introduce a frameshift mutation in Exon 4 of RelA (Figure 1A), resulting in a complete absence of the 65 kDa RelA by Western immunoblot (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Once explanation may be provided by our systems-level proteomics studies that have shown cell-type differences in innate cytokine production in response to RSV infection. Here, we observed that, although a significant amount of proteins were shared between tracheal and bronchiolar cells, the bronchiolar cells selectively secreted TSLP, CCL20 and IL6, proteins that promote Th2 and mucin expression important in the pathogenesis of RSV-induced lower respiratory tract infections (Zhao et al, 2017). These subtle differences in chemokine expression patterns by different epithelial cell types are therefore immunologically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation